Biological simplexity and cognitive heteronomy. (January 2019) - Gahrn-Andersen, Rasmus
Abstract: Heteronomy informs parts of human sense-making including perceptual and linguistic activities. This article explores Berthoz's (2012) notion of simplexity in relation to heteronomous aspects of human cognition while it criticises proponents of Active Externalism for presuming that cognitive activity is based in strong autonomy. Specifically, its negative target is the problematic aspects of Varelian Enactivism and Extended Cognitive Functionalism which are linked to the assumption that cognition is conditioned by the cogniser's strong autonomy. Since active externalists presume that cognition has a clear agent-to-world directionality, they prove unable to account for cases where cognition is informed by novel sensuous inputs. The article presents a positive argument that acknowledges the embodied basis of human sense-making as well as the weak autonomy of the cogniser. It argues that biological simplexity not only enables human enacted perception, but also underlies the embodied habits that shape the perceptual horizon that grants us being-in-the-world. This horizon has a heteronomous dimension which allows us to set up habits, orient ourselves towards unknown parts of our surroundings and engage in conversations. In fact, we are able to communicate with others because linguistic activity originates in enacted perception and sense-saturated coordination.